2021
DOI: 10.1093/ibd/izab091
|View full text |Cite
|
Sign up to set email alerts
|

Development of Balanced Whole System Value Measures for Inflammatory Bowel Disease Care in the IBD Qorus Collaborative Using a Modified Delphi Process

Abstract: Background The IBD Qorus Collaborative aims to reduce variation and increase the value of care for the adult inflammatory bowel disease (IBD) community. To evaluate the success of the collaborative, we aimed to develop a balanced set of outcome measures that reflect a multistakeholder view of value in IBD care. To achieve this, we used the Clinical Value Compass framework and engaged a mixed-stakeholder group to conduct a modified Delphi process. The end result was a 10-measure set to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…There were two primary outcomes representative of high-quality IBD treatment: clinicians with fewer patients who are prolonged steroid users and clinicians with a higher percentage of previous or current prolonged steroids users receiving steroid-sparing therapy. Both outcomes are considered quality metrics in IBD care and recommendations are to minimize use of prolonged steroids and maximize steroid-sparing therapy with immunomodulators or biologics in this context, though threshold benchmarks do not currently exist [ 9 , 16 ]. Prior data suggests that there is wide variation in the use of prolonged steroids and the use of steroid-sparing therapies [ 5 , 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were two primary outcomes representative of high-quality IBD treatment: clinicians with fewer patients who are prolonged steroid users and clinicians with a higher percentage of previous or current prolonged steroids users receiving steroid-sparing therapy. Both outcomes are considered quality metrics in IBD care and recommendations are to minimize use of prolonged steroids and maximize steroid-sparing therapy with immunomodulators or biologics in this context, though threshold benchmarks do not currently exist [ 9 , 16 ]. Prior data suggests that there is wide variation in the use of prolonged steroids and the use of steroid-sparing therapies [ 5 , 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Current organizational efforts to promote high-quality IBD clinical practices, including IBD-specialized medical home models, learning health systems, clinician education, and shared decision making initiatives are not designed to target specific clinicians or groups within healthcare networks [9][10][11]. Studies have demonstrated that higher patient volume and more specialized IBD training are associated with improved outcomes [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…These include measures of social determinants of health, disease self-management interfering behaviours, and mental health comorbidity. 7 Only about 15% of patients utilise up to 50% of healthcare resources; this is driven not solely by disease severity but also psychosocial concernschronic pain, substance abuse, depression, low social support-when identified and mitigated, outcomes and value are improved. 8 We have proposed a treat-to-target approach that includes both mucosal and emotional healing, 9 and the Disease Severity Index (DSI) is an excellent step towards truly being able to measure this (singular) target given its association with both clinical and functional outcomes.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 99%
“…As we push towards reimbursable, value‐based care in IBD, where quality is defined not only by the presence of mucosal healing but also restoration of function, metrics for disease severity require re‐calibration to include non‐clinical factors associated with disease progression, disease complications and cost of care. These include measures of social determinants of health, disease self‐management interfering behaviours, and mental health comorbidity 7 . Only about 15% of patients utilise up to 50% of healthcare resources; this is driven not solely by disease severity but also psychosocial concerns—chronic pain, substance abuse, depression, low social support—when identified and mitigated, outcomes and value are improved 8 …”
mentioning
confidence: 99%
“…Inflammatory bowel disease (IBD), is a complex and long-lasting inflammatory disease of the gastrointestinal tract that affects both grown-ups and children, including ulcerative colitis and Crohn's disease that are distinguished by their site in the bowel wall, most frequently UC affects the rectum, but then it may spread into the sigmoid, Crohn disease (CD) results in existing ulceration of any part of the gastrointestinal tract (GI) [1,2]. IBD has been widen Iraqi Journal of Industrial Research (IJOIR) all the way through the world, in evolving countries it has been categorized via the prevalence of the rate of ulcerative colitis in compared to Crohn's disease, however, in the latest years there have been reports of increased occurrence of Crohn's disease.…”
Section: Introductionmentioning
confidence: 99%